PERANCANGAN SISTEM INVENTORY BARANG BERBASIS WEB PADA GUDANG (STUDI KASUS TOKO MANASIKANA) - Alvin Satriyadi; Resti Amalia (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Design of web-based goods inventory system in warehouse (case study of manaka store). The development of technology in the digital era is currently growing rapidly, especially in the field of information and communication technology (ICT) which is currently one of the important things to improve knowledge. Therefore, creating an inventory system can help businesses manage incoming and outgoing stock sata and make it easier to make item data reports, because the management of stock item data in the manakana store is still done manually causing problems such as data discrepancies and even loss of item data and manufacturing inefficient and effective item data reports. So, the author will create a web-based inventory system using the waterfall method and the PHP framework laravel and MySQL programming languages as databases. The expected result of this research is to make it easier for manakana store to manage stock data and make goods data reports.